The seventh queen : a novel - Kelly, Greta (Harper Voyager, an imprint of HarperCollinsPublishers, 2021)
"The Empire of Vishir has lost its ruler, and the fight to save Seravesh from the Roven Empire is looking bleak. Moreover, Askia has been captured by power-hungry Emperor Radovan, who plans on making her his wife simply so he can take her magic as his own, killing her in the process...The jewel Radovan has put around her neck will pull her power from her in thirty days. Worse, Vishir might not even have that long, as the two heirs to the throne are on the verge of civil war"--